2007
DOI: 10.1073/pnas.0708970104
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptors and stargazin-like transmembrane AMPA receptor-regulatory proteins mediate hippocampal kainate neurotoxicity

Abstract: Naturally occurring glutamate analogs, such as kainate and domoate, which cause excitotoxic shellfish poisoning, induce nondesensitizing responses at neuronal ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors. In addition to acting on AMPA receptors, kainate and domoate also activate high-affinity kainate-type glutamate receptors. The receptor type that mediates their neurotoxicity remains uncertain. Here, we show that the transmembrane AMPA receptor-associated protein (TARP) ␥-2 (or starga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…Thus, our data would seem to support the hypotheses that ApoD may have a role in maintaining the glutamatergic function in the mammalian CNS. This hypothesis is consistent with previous data showing that exogenous ApoD can help protect against the neurotoxic effects of kainic acid (He et al, 2009), some of which are mediated by KAR (Garthwaite and Wilkin, 1982) and AMPAR (Tomita et al, 2007). It has been previously shown that ApoD -/-mice have complex,…”
Section: Discussionsupporting
confidence: 81%
“…Thus, our data would seem to support the hypotheses that ApoD may have a role in maintaining the glutamatergic function in the mammalian CNS. This hypothesis is consistent with previous data showing that exogenous ApoD can help protect against the neurotoxic effects of kainic acid (He et al, 2009), some of which are mediated by KAR (Garthwaite and Wilkin, 1982) and AMPAR (Tomita et al, 2007). It has been previously shown that ApoD -/-mice have complex,…”
Section: Discussionsupporting
confidence: 81%
“…No differences were found in KA-treated cultures compared with untreated cultures (data not shown), indicating that KA was not toxic under our experimental conditions. This is consistent with the suggestion that KAinduced activation of AMPARs, rather than KARs, is mostly responsible for KA excitotoxicity (Tomita et al, 2007). We also measured KA-induced currents in the three stages of maturation and found that KA (30 M; Ϫ60 mV of holding potential) induced ionotropic responses in ϳ70 -75% of cells studied with amplitudes that were not significantly different among the three different maturation stages.…”
Section: Kars Bidirectionally Modulate Neuronal Maturationsupporting
confidence: 70%
“…4,5,[25][26][27] Quercetin attenuates in vitro and in vivo excitotoxin-mediated insults. 15,16,39,40) The present findings on the inhibitory effects of quercetin on AMPA receptor channel activity with voltage-dependent manner might be one of the main contributors to neuroprotection against AMPA receptor-related neurotoxicity.…”
Section: Current and Voltage Relationship In The Inhibitory Effect Ofmentioning
confidence: 99%
“…4,5,10,[25][26][27] Agents that regulate ionotropic glutamate receptor channel currents are studied for the development of neuroprotective agents through natural sources or synthesis. As a natural source, quercetin is one of several flavonoids and is a well-known anti-oxidant.…”
Section: Current and Voltage Relationship In The Inhibitory Effect Ofmentioning
confidence: 99%